Do Auditor Professional Scepticism and Client Narcissism Affect Fraud Risk Assessment? - Rijadh Djatu Winardi; Arizona Mustikarini; Yoga Pernama (The Indonesian Journal of Accounting Research, 2017)
Abstract: This study investigates the effect of professional skepticism and client narcissism on auditors’ fraud risk assessment. Financial reporting fraud has become a concern for auditors as part of their responsibility. Auditors are expected to assess the risk of fraud as well as its impact on financial reporting. During fraud risk assessment, several factors can influence auditors, namely professional skepticism as an internal factor and client's narcissism as an external factor. Professional skepticism is related to the level of details and awareness to conduct assessment work. Narcissistic clients are more likely to demonstrate higher inherent and control risk. The purpose of this study is to investigate the effect of professional skepticism and client narcissism on auditors’ fraud risk assessment. This study employs a 2x2 between-subjects experimental design, where professional skepticism and client narcissism are manipulated into are high and low level. The participants in this study are 107 accounting students from undergraduate, master, and professional program in a major university in Indonesia. The results of this study suggest that auditors with a higher level of professional skepticism are more sensitive to the higher incident of fraud and client's narcissism positively affect auditors’ assessment of fraud risk. This study contributes to the current fraud risk assessment literature, particularly within Indonesian auditing profession. Abstrak: Penelitian ini menyelidiki efek skeptisisme profesional dan narsisme klien pada penilaian risiko penipuan auditor. Pelaporan keuangan penipuan telah menjadi perhatian bagi auditor sebagai bagian dari tanggung jawab mereka. Auditor diharapkan untuk menilai risiko penipuan serta dampaknya pada pelaporan keuangan. Selama penilaian risiko penipuan, beberapa faktor dapat mempengaruhi auditor, yaitu skeptisisme profesional sebagai faktor internal dan narsisisme klien sebagai faktor eksternal. Skeptisisme profesional terkait dengan tingkat rincian dan kesadaran untuk melakukan pekerjaan penilaian. Klien narsistik lebih mungkin untuk menunjukkan risiko yang melekat dan kontrol yang lebih tinggi. Tujuan dari penelitian ini adalah untuk menyelidiki efek skeptisisme profesional dan narsisisme klien pada penilaian risiko penipuan auditor. Penelitian ini menggunakan 2 x 2 desain eksperimental antar subyek, di mana skeptisisme profesional dan narsisisme klien dimanipulasi menjadi tinggi dan rendah. Para peserta dalam penelitian ini adalah 107 mahasiswa akuntansi dari program sarjana, master, dan profesional di universitas besar di Indonesia. Hasil penelitian ini menunjukkan bahwa auditor dengan tingkat skeptisisme profesional yang lebih tinggi lebih sensitif terhadap insiden penipuan yang lebih tinggi dan narsisisme klien secara positif memengaruhi penilaian auditor terhadap risiko penipuan. Studi ini berkontribusi pada literatur penilaian risiko penipuan saat ini khususnya dalam profesi audit Indonesia.